Android-Powered Home Lighting: A Control and Monitoring System for Smart Living - Sobri, Arifian; Mualim, Wildan; Riswandha, M. Noval (Journal of Information Technology application in Education, Economy, Health and Agriculture, 2024)
This research aims to address the manual control and maintenance of community lights by developing a remote light controller and detector using the Internet of Things (IoT) concept. The process involves the use of an Android-based smartphone application to control and monitor the lights. The system utilizes a lamp current, which is charged on the ledge, and a relay driver to turn the lights on or off. The Wemos microcontroller, with the ESP8266 Wi-Fi module, serves as the link between the smartphone and the server. The results of the research show that the photodiode light sensor operates effectively when activated, and the current sensor can determine the number of lights that are turned off. Users can access the control and monitoring of the lights through the Android application, allowing them to control the lights remotely and keep track of the number of lights that are functioning properly